INTEGRASI ARTIFICIAL INTELLIGENCE DALAM KURIKULUM MERDEKA PADA SEKOLAH MENENGAH KEJURUAN - Syifa Martina Putri, Syauqiyah; Suci Rahmawati, Rizki; Azizul Hakim, Muhammad; Deva Bela Negara, Raga; Anugrah Firdaus, Genta; Wildan Habibi, Mohammad (STKIP Subang, 2026)
The development of Artificial Intelligence (AI) in education has become a driving factor in the transformation of learning in Vocational High Schools (SMK), particularly in the implementation of the Independent Curriculum, which emphasizes flexible, student-centered, and technology-based learning. This study aims to analyze the integration of Artificial Intelligence in the Independent Curriculum in vocational high schools and identify the benefits and challenges in its implementation. The research method used is a qualitative approach through a literature review by reviewing various relevant scientific articles from 2023–2025. The results of the study indicate that the use of Artificial Intelligence, such as in the creation of teaching modules, interactive learning media, and the use of generative Artificial Intelligence in the learning process, can improve learning effectiveness, cognitive competence, creativity, and student work readiness in the digital era and Society 5.0. In addition, Artificial Intelligence integration also supports the implementation of project-based and problem-based learning, which align with the principles of the Independent Curriculum. However, its implementation still faces various obstacles, such as limited technological infrastructure, teacher readiness and competence, and the suboptimal policies and integration of the Artificial Intelligence -based learning system. Therefore, a targeted strategy is needed, strengthening teacher training, and developing educational infrastructure and policies so that the integration of Artificial Intelligence in the Independent Curriculum can run optimally in improving the quality of education in vocational schools.